Practical Wisdom: On Theological Teaching and Learning – Edited by Malcolm L. Warford - Lai, Alan Ka Lun (Teaching theology and religion, 2006)
Books reviewed: Practical Wisdom: On Theological Teaching and Learning. Edited by Malcolm L. Warford. New York, N.Y.: Peter Lang Publishing, Inc., 2004. xiv + 283 pages. ISBN 0-8204-7263-8.